Content Analysis of Biology Learning Objectives in Merdeka Curriculum: Detection of Misconceptions and Terminological Interference from Predecessor - Eva Nauli Taib; Rostina Taib; Evinopita Taib (Postgraduate, University of Mataram, 2025)
Indonesia's shift from Curriculum 2013 to the Merdeka Curriculum has introduced significant challenges in biology education, particularly in formulating competency-based learning objectives. This study analyzes professional misconceptions in learning objectives using qualitative content analysis of eight curriculum documents—lesson plans and teaching modules—focused on